Antimicrobial resistance prevalence of Escherichia coli and Staphylococcus aureus amongst bacteremic patients in Africa: a systematic review. (March 2023) - Haindongo, Erastus Hanganeni; Ndakolo, Diana; Hedimbi, Marius; Vainio, Olli; Hakanen, Antti; Vuopio, Jaana
ABSTRACT: Objectives: Antimicrobial resistance (AMR) is a global concern among infectious diseases. Bloodstream infections can potentially become life-threatening if they become untreatable with conventional antimicrobials. This review aims to provide an understanding of the AMR prevalence and trends of common bacteremic pathogens, namely Escherichia coli and Staphylococcus aureus in the World Health Organization (WHO) Africa region. Methods: PubMed and Google Scholar were searched using relevant keywords for published human studies (excluding case reports and reviews) reporting bacteremic AMR data on the pathogens of interest between 2008 and 2019. Two reviewers independently screened the articles against a pre-defined eligibility criterion. Data extraction and analysis were achieved with different platforms: Covidence, Excel, R version 3.6.3, and QGIS v3.4.5. The pooled prevalence, 95% confidence intervals, and I 2 index (a measure of heterogeneity) were calculated for the various pathogen-antibiotic combinations. Results: Five hundred sixty-two papers were retrieved, with 27 papers included in the final analysis. Only 23.4% (11/47) of member states of the WHO African region had reports on AMR in bacteremia. The Clinical and Laboratory Standards Institute (CLSI) (78.5%) was the most common standard used in the region. For E. coli, the pooled resistance was: cefotaxime (42%), imipenem (4%), meropenem (0%), and colistin (0%). For S. aureus, the calculated pooled resistance was cloxacillin (34%), oxacillin (12%), and vancomycin (0%). There was a high degree of variation across studies ( I 2 > 90%). Conclusion: The pooled resistance rates indicate a concerning degree of methicillin-resistant and Extended Spectrum-ß-lactamase–producing pathogens. The paucity of AMR data also presents challenges for a comprehensive understanding of the situation in the region. Continent-wide and standardized surveillance efforts therefore need strengthening.